Virtual Reality Volumetric Rendering Using Ray Marching with WebGL - Marino, Federico (2021)
This work is concerned with virtual reality web applications that implement volumetric visualizations based on Ray Marching, combined with traditional triangle-based rendering. The use case selected was an interactive tool to navigate through a 3D model of sedimentary basins and natural reservoirs of oil and gas. The surfaces are described by signed distance functions computed in the GPU within a pixel shader. A procedural 3D texture defines the distribution of sedimentary strata inside the volume and provides visual clues of the internal structures. In VR mode, the user can navigate the scene by moving his body. He can subtract portions of the 3D volume in real time through a set of Boolean operators (plane, cylinder or sphere) using VR hand controllers. A virtual control panel, dynamically generated from a JSON file, allows parameters to be adjusted within VR. The application can also be used in desktop mode.